Survive IT! Survival analysis of IT project planning approaches - Zsolt T. Kosztyán; Róbert Jakab; Gergely Novák; Csaba Hegedîus (Operations Research Perspectives, 2020)
Despite the emerging importance of IT projects and the application of new flexible project management approaches, such as agile and hybrid methodologies, there are still many unsuccessful projects. Therefore, it is important to study which risk factors have the highest influence on the success and survivability of IT projects, how they are related to each other, and which project planning and management approaches can mitigate project risk the most. The goal of the study is twofold. On the one hand, a new risk analysis tool is proposed that handles the project flexibility and the dependency of the risk factors at the same time. On the other hand, with the proposed risk analysis tool, the effects of project management approaches for scheduling performance and risk mitigation are analyzed. With the proposed risk management tool, we determined the level of flexibility that allows flexible project management methods to gain advantage over traditional methods. In addition, we answer whether it makes sense to apply flexible planning for non-IT projects.
Keywords: 330; Flexible project management approaches; Meta-network analysis; Project risk; Risk mitigation